Comparing clinical presentation, viremia, and immunological factors at various severity presentations in hospitalized children affected by COVID‐19: A cross‐sectional study - Marzieh Jamalidoust; Seyedeh Sedigheh Hamzavi; Eslam Shorafa; Mandana Namayandeh; Laiba Batool; Seyedeh Narges Abootalebi (Health Science Reports, 2023)
Abstract Background and Aims Although SARS‐CoV‐2 infection usually leads to mild COVID‐19 in children, sometimes it causes serious complications, especially in those with underlying diseases. Several factors have been identified in determining disease severity in adults, and limited studies have been conducted in children. The prognostic implications of SARS‐CoV‐2 RNaemia as an important factor in determining disease severity in children are not well understood. Methods In this study, we aimed to prospectively assess the relationship between disease severity and immunological factors and viremia in 47 COVID‐19 hospitalized children. In this research, 76.5% of children experienced mild and moderate COVID‐19, while 23.5% experienced severe and critical forms of the disease. Results The presence of underlying diseases in different groups of pediatric patients differed significantly from each other. On the other hand, clinical symptoms such as vomiting and chest pain as well as laboratory parameters including erythrocyte sedimentation rate were significantly different in different groups of patients. Viremia was seen in only two children, and this had no significant relationship with the severity of COVID‐19. Conclusion In conclusion, our data confirmed that COVID‐19 severity differed in SARS‐CoV‐2 infected children. Some clinical presentation and lab data parameters were different in various presentation of patients. Viremia was not associated with severity in our study.